2006
DOI: 10.1080/13625180600766032
|View full text |Cite
|
Sign up to set email alerts
|

On the use of contraceptive methods among married women in Turkey

Abstract: Women's behaviours on contraceptive method use and choice are associated with women's attitude towards family planning and level of education as well as region and place of residence; that is, ease of access to the methods. To increase success of family planning programmes, it should be ensured that the methods are easily accessed and women receive information about contraceptive methods. In addition, family planning providers must strive to increase women's level of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
2
15
1
Order By: Relevance
“…However, young adults were hesitant to use FP due to concerns about short-and long-term side effects. These findings are similar to those from studies conducted in Egypt and Turkey, where young adult women were not using contraception due to fears of side effects (Alpu & Fidan, 2006;Kotb Sultan et al, 2010). Our participants were also sceptical of contraceptive effectiveness as many describe contraceptive failure to be a common phenomenon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, young adults were hesitant to use FP due to concerns about short-and long-term side effects. These findings are similar to those from studies conducted in Egypt and Turkey, where young adult women were not using contraception due to fears of side effects (Alpu & Fidan, 2006;Kotb Sultan et al, 2010). Our participants were also sceptical of contraceptive effectiveness as many describe contraceptive failure to be a common phenomenon.…”
Section: Discussionsupporting
confidence: 92%
“…In summary, our findings indicate that urban young adults need more information on various FP options, the prevalence and severity of known contraceptive side effects, and where to seek help for side effects (Alpu & Fidan, 2006;Bajwa, Bajwa, Ghai, Singh, & Singh, 2011;Ijaiya, Raheem, Olatinwo, Ijaiya, & Ijaiya, 2009;Wood & Jewkes, 2006). A recent literature review of modern contraceptive use from qualitative studies summarised similar obstacles to women's use of contraception, including a lack of knowledge, access and a fear of side effects (Williamson, Parkes, Wight, Petticrew, & Hart, 2009).…”
Section: Discussionmentioning
confidence: 70%
“…A previous study from Turkey investigated the possible factors affecting contraceptive choice of married women. Use of modern methods (IUD, COC, condom, BTL, implant) was found more common in middle-aged women, living in urban areas and with higher education [23]. Another research suggested that empowerment of Turkish women (the more educated, those with better socioeconomic status, and those living in less crowded households resort) increases use of modern contraceptives [24].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies supporting this in the literature. Alpu and Fidan (2006) studied the factors affecting the contraceptive choice of married women and they found that religion was the most effective factor, followed by living region and educational status. They indicated that the use of modern methods increased in those who were higher educated and who lived in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of contraception methods and the factors affecting women's choices there were different results according to the region where the women lived, the working conditions, educational status and age groups (Alpu and Fidan, 2006;Topsevar et al, 2006;Mosher and Jones, 2010).…”
mentioning
confidence: 99%